2021
DOI: 10.1111/echo.15240
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of fetal ventricular function by speckle tracking echocardiography

Abstract: Methods:The study included 59 patients with normal fetal heart structure, blood flow, and heart rhythm (fetal abnormality-negative group) and 50 patients with abnormal fetal heart structure, blood flow, and/or heart rhythm (fetal abnormality-positive group). Automated Cardiac Motion Quantification (aCMQ) was performed in both groups to obtain left and right ventricular endocardial global longitudinal strain (GLSendo), mid-myocardial global longitudinal strain (GLSmid), and epicardial global longitudinal strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
(46 reference statements)
3
7
0
Order By: Relevance
“…Most quantitative fetal echocardiographic techniques for assessing myocardial function have similar limitations in the fetus as they do in the postnatal heart, which includes finite reproducibility resulting from challenges in obtaining correct alignment ( 78 ). In common with most non-invasive methods for assessing myocardial function, standard echocardiographic parameters such as ejection fraction or ventricular fractional area change are representative of the load-dependent pumping function of the ventricle, rather than cardiomyocyte contractility or changing cavity pressure in the fetal heart ( 79 , 80 ). Evaluation of strain rate, on the other hand, mainly reflects maturational changes in the myocardium while being relatively independent of loading conditions ( 81 ).…”
Section: Approaches To Assessing Cardiac Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most quantitative fetal echocardiographic techniques for assessing myocardial function have similar limitations in the fetus as they do in the postnatal heart, which includes finite reproducibility resulting from challenges in obtaining correct alignment ( 78 ). In common with most non-invasive methods for assessing myocardial function, standard echocardiographic parameters such as ejection fraction or ventricular fractional area change are representative of the load-dependent pumping function of the ventricle, rather than cardiomyocyte contractility or changing cavity pressure in the fetal heart ( 79 , 80 ). Evaluation of strain rate, on the other hand, mainly reflects maturational changes in the myocardium while being relatively independent of loading conditions ( 81 ).…”
Section: Approaches To Assessing Cardiac Functionmentioning
confidence: 99%
“…By contrast with movement, strain and especially Lagrangian strain [strain relative to initial length, i.e., a single reference length field ( 12 )] and its velocity (strain rate) are not dependent on adjacent regions, making them more accurate than simple velocity measurements ( 71 , 77 , 96 , 119 , 120 ). Strain measurements, influenced by extrinsic loading and intrinsic contractile force ( 14 , 71 ), consider the contractility of the cardiomyocytes and changes with cardiac cavity pressure ( 79 ). Longitudinal strain and strain rate seem to reflect the fetal right ventricular dominance with strain and strain rate values between 1 and 1.5 times higher in the right compared to the left ventricle ( 121 ).…”
Section: Approaches To Assessing Cardiac Functionmentioning
confidence: 99%
“…A significant correlation between the endoGLS and the gestational age (GA) is controversially debated in the current literature. Both, an increase and a decrease in endoGLS as well as constant values have been reported previously with advancing GA [2,3,10,14,19,25,[27][28][29]. These conflicting data regarding normal reference ranges and changes of endoGLS complicate the interpretation of current results [14].…”
Section: Introductionmentioning
confidence: 65%
“…In numerous second-trimester and third-trimester fetal heart studies, fetuses with congenital heart disease have demonstrated reduced ventricular myocardial longitudinal strain [7,18,19] . Compared with conventional echocardiography, STI technology can more sensitively assess changes in cardiac function in adults and children by measuring myocardial deformation parameters [12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Screening for fetal cardiac malformation in the early second trimester is accurate [5] , and it is feasible and clinically signi cant to move the time window of prenatal diagnosis of fetal congenital heart disease forward. A large number of studies have shown that fetal cardiac function evaluation has important clinical value in the management and prognosis of gestational hypertension, gestational diabetes mellitus, and fetal congenital heart disease, among other diseases [6][7][8][9] . However, most studies have focused on the ultrasound assessment of fetal cardiac structure and function in the second or third trimesters, while few studies have focused on fetal cardiac function before 18 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%